Self Me: Interpretation of Self-Injury in the Context of Healing - Hanna Medita; Nazima Rangwala Kalita (Pascasarjana Institut Seni Indonesia Surakarta, 2021)
The work Self Me focuses on the topic of self-injury, which is influenced by a number of factors, including bullying and mild to severe stress. The purpose of this study is to process the expression of pain from self-injury into a dance work. Self Me is in the form of research-based work using asymmetrically arranged wood and ropes as a medium for symbolic expression. The dancers involved use one dancer who represents several backgrounds. There are five segments of Self Me's work, the first is how a person tries to accept life symptoms that can become self-injury. The second segment is the feel-good phase of self-injury. The third segment expresses comfort in solitude, the fourth is about being stuck with problems that are difficult to get out of and the fifth expresses various emotions asynchronous feelings and thoughts. This research revealed self-concept findings, meaning that difficulties may be overcome when we confront ourselves. All issues and answers that decide are self, thus self means self and I means myself